Modern aspects of competitiveness in Kazakhstan - Syzdykova, D.I.; Syzdykova, E.Zh.; Assanova, M.K.; Dauletova, A.M. (BUKETOV BUSINESS REVIEW, 2020)
Object: The purpose of this study is to determine the degree of influence of various economic indicators on the competitiveness of Kazakhstan’s economy. To identify the challenges of competitiveness’ establishment. At the moment, there is a need to find ways to increase the competitiveness of domestic economy in the light of Kazakhstan’s integration into the world. The purpose of the study is to identify the features of the competition development in the modern economy of Kazakhstan. The object of the study are the aspects of competition in the economy of Kazakhstan. The subject of the study are the peculiarities of competition in Kazakhstan as an integral feature of a market system that can positively affect the country’s economic growth. Methods: statistical and comparative analysis. Findings: This article explores aspects that affect competitiveness. Performed was the analysis of indicators on the global competitiveness rating, foreign direct investment (FDI) for the period of 2009–2019 for such countries as Kazakhstan, Russia, Azerbaijan, and Kyrgyzstan. FDI is an indicator of the “confidence” of investment by large companies. Studied were the indicators of the innovation index and the costs of research and development for the period of 2011–2019. Conclusions: Globalization and the post-industrial era require Kazakhstan to increase competitiveness. At this stage of development, innovative methods of increasing the economy are becoming more and more sought after. The results of the study allow us to conclude which of the listed aspects affect the competitiveness of the domestic economy. These results are very important for decision making within the economy.